Experimental Investigation on the Utilization of Marble and Scoria Powder as Partial Replacement of Cement in Concrete Production - Tadele Yigrem Zeleke; Kassahun Admassu Abegaz; Begashaw Worku Yifru; Dagmawi Tesfaw Yitayew (Advances in Civil Engineering, 2023)
This paper explores how marble and scoria powder can be used as partial substitutes for ordinary Portland cement in creating C-25 concrete. Both materials contain over 50% of the major oxides found in cement, with marble high in CaO and scoria high in SiO2. Experimental investigations were conducted to study the chemical, physical, mechanical, and fresh properties of concrete containing marble and scoria powder. For the investigation, 13 different mixes, including the control mix, were used with a constant water–cement ratio of 0.5 and a slump range of 25–50 mm for concrete with a compressive strength (CS) of 25 MPa. Marble-to-scoria ratio of 2 : 1, 1 : 1, and 1 : 2 was used, and then the combined fraction of both marble waste and scoria in concrete was increased from 0% to 20% in 5% range. Including the control test specimens, a total of 117 (150 × 150 × 150 mm) concrete cubes for CS test, 39 (100 × 100 × 500 mm) concrete beam specimens for flexural strength test, 39 (100 × 200 mm) cylinder specimens for splitting tensile strength (STS) test and, 39 (100 × 100 × 100 mm) cube specimens for water absorption test were cast and tested at 3, 7, 28, and 56 days. The test results indicate that marble and volcanic scoria powders with marble-to-scoria ratio of 1 : 1 could replace cement up to 15% without compromising the CS and up to 10% without compromising the flexural and STS; also, the water absorption decreases up to 10% replacement; however, the workability of the fresh mix decreases as the combined replacement level of marble and scoria increases. Generally, a 10% replacement with marble-to-scoria ratio of 1 : 1 produces concrete with higher compressive, flexural, tensile strength, and water absorption manifestations when compared to conventional concrete.